How future thinking can derail your company's present - Yu, Howard; Meister, Alyson (MIT Sloan Management Review, 2022)
As companies strive to become future-ready, they can sometimes lose sight of the factors that have enabled their current success, including their core customers. The authors discuss four common mistakes leaders make as they strategize for the future, along with real-world examples of companies whose growth strategies paid off.
Keywords: Success in business; Business forecasting; Succès dans les affaires; Prévision commerciale